H+-selective electrode for the determination of subzero pH values - Siamionau, Andrei V.; Egorov, Vladimir V. (Journal of the Belarusian State University. Chemistry, 2023)
The theory of functioning in acidic region of H+-selective electrodes based on amine-type neutral carriers, as well as general ways to shift the upper detection limit to acidic region, such as varying the nature of nitrogen atom substituents to target lower basicity, optimal plasticiser choice and the usage of the ion exchanger that is stable in acidic solutions, namely, potassium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate are considered. The electrode based on original ionophore that is N-phenyl-N-[(3,4,5-tris-dodecyloxyphenyl)methyl]ethanamine functioning to determine subzero pH values was studied. A method to determine pH of the upper detection limit for electrodes based on ionophores with low basicity is suggested. The method is based on usage of equally transferring solutions of mixed electrolyte that eliminates diffusion potential. The usage of silver wire covered with electrodeposited silver chloride as a reference electrode that increases the measurements sensitivity in hydrochloric acid solutions is considered. It was shown that the H+-selective electrode elaborated is suitable for pH determination in hydrochloric acid solutions down to –1.5 that corresponds to 4 mol/L solution.
Keywords: ion-selective electrode; pH determination; strongly acidic solution; ionophore; diffusion potential